Nanoscopic insights of saline water in carbon nanotube appended filters using molecular dynamics simulations. Issue 16 (8th April 2019) - Sahu, Pooja; Musharaf Ali, Sk.; Shenoy, K. T.; Mohan, S.
Abstract : Nanotube appended membranes are shown to be very promising due to their ultrafast water transport and very high salt rejection ability. Abstract : Nanotube appended membranes are shown to be very promising due to their ultrafast water transport and very high salt rejection ability. Using classical molecular dynamics, the present study reports the nanoscopic assessment of various molecular events for nanotube-based desalination, which might be useful for nanoscale devices during process operation at the macroscopic scale. The characteristics of water and ion flow are discussed with varied strength of pressure gradient and salt concentration for different scales of confinement. The results revealed that the membranes comprising nanotubes of 1.0–1.1 nm diameter can be optimized for efficient water desalination with more than >95% salt rejection. Furthermore, the anomalies in water flux through nanotubes are linked with the hydration characteristics of ions inside CNTs. The results show the maximum hydration of confined ions inside the nanotubes, which indicated the minimum permeability of water due to freezing effects. Furthermore, the MD results revealed that akin to bulk phases, the mass transport through nanotubes can be linked with the component diffusivity in the medium. It has been demonstrated that not only the diffusivities of water and ions, but even the gradient of water to ion diffusivity might be utilized to predict and explore the experimental observations, which might be helpful in optimizing the operational regime in nanotube-based filtrations. Moreover, the thermodynamic characteristics of the flow are discussed in terms of the entropy of water and ions using the robust two-phase thermodynamic (2PT) method. The results reflect that the entropy of water is linked to the distortion of the hydrogen bond network inside the nanotube confinement, at the nanotube–water interface and at the bulk solution, whereas the entropy of ions seems to be majorly dominated by their oscillation. Also, the interconnection of hydration structure, mass flux and the diffusivity of water and ions along with their thermodynamic origin are discussed.